Effect of Job Insecurity, Employee Engagement and Job Performance on Employee Turnover Intention Non-Civil Servant Government at District Court in Southeast Sulawesi Region - Zaky, Achmad; Markonah, Markonah; Suryanto, Suryanto (Dinasti Publisher, 2025)
This study aims to determine the influence of Job Insecurity, Employee Engagement and Job Performance to Turnover Intention on Government employees Non-Employee Government Court Country in region Southeast Sulawesi. This study uses a quantitative approach through the distribution of questionnaires and the application of SPSS IBM 26 involving 68 respondents from 9 District Courts in the Southeast Sulawesi region. t-Test Results shows that there is a positive and significant influence of job insecurity on turnover intention. However, employee engagement does not have a significant influence on turnover intention, and job performance has a positive influence on turnover intention. Job insecurity, employee engagement and job performance simultaneously have a positive and significant influence on turnover intention recommended for increase Engaged on PPNPN given reward so that more enthusiastic in Work, given training and guidance so that Can by test PPPK and National Civil Service Candidate.